Analisis Penetapan Tarif Sewa Kamar Dengan Cost Plus Pricing Pendekatan Full Costing Pada Hotel Grand Yuda Di Tenggarong - Anggareni, Aji Desilia (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2017)
Abstract: This research was conducted at Hotel Grand Yuda In Tenggarong, this research is about the gauge cost of goods sold which are issued by Grand Yuda Hotel appropriately, so that it can determine the amount of room rental rates Grand Yuda Hotel. The main purpose of this research is to determine the amount of room rental rates applied all this time is appropriate or not of the according to accounting rules. The data analysis techniques used were descriptive analysis and comparative analysis. The results of this research showed that there are differences in the determination of room rental rates according to the Grand Yuda Hotel with the results of the researchers’ calculations which use cost plus pricing method full costing approach. The determination of the room rates conducted by Grand Yuda Hotel for the room with types executive, deluxe, superior, and standard is higher than room rate according to the theory the difference was more than 5%. Keywords: Rent Room Rates, Cost Plus Pricing, Full Costing